Regional Epidemiology of Methicillin-Resistant Staphylococcus aureus Among Adult Intensive Care Unit Patients Following State-Mandated Active Surveillance. (7th December 2017) - Lin, Michael Y; Hayden, Mary K; Lyles, Rosie D; Lolans, Karen; Fogg, Louis F; Kallen, Alexander J; Weber, Stephen G; Weinstein, Robert A; Trick, William E; ,
Abstract : Among critically ill adults, the prevalence of methicillin-resistant Staphylococcus aureus (MRSA) colonization did not decline following implementation of state-legislated active surveillance, suggesting the limits of active surveillance legislation in reducing MRSA colonization burden in this population. Abstract: Background: In 2007, Illinois became the first state in the United States to mandate active surveillance of methicillin-resistant Staphylococcus aureus (MRSA). The Illinois law applies to intensive care unit (ICU) patients; contact precautions are required for patients found to be MRSA colonized. However, the effectiveness of a legislated "search and isolate" approach to reduce MRSA burden among critically ill patients is uncertain. We evaluated whether the prevalence of MRSA colonization declined in the 5 years after the start of mandatory active surveillance. Methods: All hospitals with an ICU having ≥10 beds in Chicago, Illinois, were eligible to participate in single-day serial point prevalence surveys. We assessed MRSA colonization among adult ICU patients present at time of survey using nasal and inguinal swab cultures. The primary outcome was region-wide MRSA colonization prevalence over time. Results: All 25 eligible hospitals (51 ICUs) participated in serial point prevalence surveys over 8 survey periods (2008–2013). A total of 3909 adult ICU patients participated in the point prevalence surveys, with 432 (11.1%) found to be colonized with MRSA (95% confidence interval [CI], 10.1%–12.0%). The MRSA colonization prevalence among patients was unchanged during the study period; year-over-year relative risk for MRSA colonization was 0.97 (95% CI, .89–1.05; P = .48). Conclusions: MRSA colonization prevalence among critically ill adult patients did not decline during the time period following legislatively mandated MRSA active surveillance. Our findings highlight the limits of legislated MRSA active surveillance as a strategy to reduce MRSA colonization burden among ICU patients.